Analisis Perilaku Penelusuran Informasi pada Generasi Milenial Dalam Memenuhi Kebutuhan - Rahima Husna; Franindya Purwaningtyas (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
The millennial generation is a generation that is very familiar with the use of information technology, which cannot be separated from the use of gadgets and the internet in their daily life. However, how is the behavior of the millennial generation in meeting their need for information. This article also describes the models in information browsing behavior that are commonly known. Then the information behavior that appears in today's millennial generation in fulfilling information related to information: lifestyle, lectures, general information, social life, health and future plans. Keywords: millennial generation, information seeking behavior, information needs.